Hip fracture incidence in Japan: estimates of new patients in 2007 and 20-year trends - Orimo, Hajime (Springer-Verlag, 2009)
SUMMARY: We estimated the number of hip fracture patients in 2007 in Japan and investigated the trends in incidence during a 20-year period from 1987 to 2007. Despite the increasing number of new patients, the incidence of hip fracture in some age groups showed the possibility of decline. PURPOSE: The aims of this study were to estimate the number of hip fracture patients in 2007, to investigate the trends in incidence during a 20-year period from 1987 to 2007, and to show the regional differences in Japan. METHODS: Data were collected through a nationwide survey based on hospitals by the mailing method. Hip fracture incidences by sex and age and standardized incidence ratios by region were calculated. RESULTS: The estimated numbers of new hip fracture patients in 2007 were 148,100 in total (95% CI, 144,000–152,200), 31,300 (30,500–32,100) for men, and 116,800 (113,900–119,700) for women. The incidence rate in men aged 60–69 years and that in women aged 60–79 years were the lowest in the 15-year period from 1992 to 2007. The incidence was higher in western areas of Japan than in eastern areas in both men and women. CONCLUSIONS: Despite the increasing number of new patients, the incidence of hip fracture in some age groups for both men and women showed the possibility of decline. The exact reasons for this are unknown, but drug therapy for osteoporosis and fall prevention programs might have influenced the results. Some nutrient intakes might explain the regional differences not only in Japan but also in some other countries.